Avaliação in vitro da inclusão do líquido da casca da castanha de caju em dietas para ruminantes - García Díaz, Tatiana (2013)
Plant extracts, mainly functional oils, are considered alternative additives that can improve the microbial metabolism, ruminal fermentation characteristics and diet's digestibility in ruminants. The liquid extracted from the cashew nutshell (CNSL) is a functional oil characterized for being a natural source of unsaturated long-chain phenolic compounds. The CNSL may be able to positively influence the digestibility of the diet and induce changes on the end-products of fermentation in the rumen. Although some of the effects of CNSL have already been demonstrated, the available studies on the oil are still limited, so future research to examine the benefits of CNSL in the nutrition of ruminants are required. The objective of this study was to evaluate the effect of cashew nutshell liquid (CNSL) in ruminants diets containing increasing levels of concentrate on in vitro dry matter digestibility (IVDMD), and also on in vitro cumulative gas production kinetic, parameters of rumen fermentation, ammonia-N (NH3-N) and ruminal pH. The experimental design was completely randomized in a factorial arrangement 5x4+ 1, with five levels of concentrate (200, 400, 600, 800 and 1000 g/kg) and four levels of CNSL (0, 0.3, 0.6 and 1.2 g/kg) and a control diet composed only by roughage, totalizing 21 treatments. Corn silage was used as forage and ground corn, soybean meal, urea and mineral supplement as concentrated ingredients. An interaction was observed (P≤0.01) between the levels of CNSL and the concentrate on the IVDMD, rapid degradation fraction (fraction A), lag time and total gas production. The inclusion of concentrate increased the (P≤0.05) IVDMD linearly, while levels of CNSL resulted in a quadratic effect (P≤0.001) on this variable, being estimated the point of maximum IVDMD at the inclusion of 5 g of CNSL /kg of concentrate. The total gas production, the fraction of slow degradation (fraction D) and accompanying degradation rate (fraction E) increased linearly (P≤0.01) when levels of concentrate increased. Levels of CNSL did not influence (P>0.05) the parameters of gas production when analyzed simultaneously in all diets with the inclusion of concentrate. The levels of concentrate resulted in a linear increase (P<0.001) of NH3-N concentrations and a reduction (P<0.001) in ruminal pH. CNSL levels decreased (P<0.001) the concentration of NH3-N and increased (P<0.001) ruminal pH. There was a high correlation between the total gas production and disappearance of the substrate (r =0 .94), indicating that the production of gas may be a precise technique for estimating the curve of digestibility of foods. The inclusion of 0.5 g of CNSL /kg of concentrate in high concentrate diets improves IVDMD, reduces the production of ammonia, and avoids drastic reductions in ruminal pH resulting from the addition of concentrated ingredients. These results improve the utilization of. nutrientes.